Is there a funding bias in biomedical research? - Roig-Loscertales, Francesc (THEORIA. An International Journal for Theory, History and Foundations of Science, 2026)
The observation that studies funded by the pharmaceutical industry tend to report results more frequently favorable to the sponsor has led to the suggestion of a funding bias that could overestimate the effects of medications. However, no clear mechanism has been identified, and there is a lack of compelling evidence that industry funding introduces a systematic error in the results that favors its interests. This article provides a critical review of the concept of funding bias, arguing that industry influence should not be regarded as a distinct form of bias. Drawing on the definition of bias established by the Cochrane methodology—widely considered the gold standard in the evaluation of health interventions—the analysis explores the characteristics that industry influence would need to meet in order to be considered a source of bias in clinical research. Using an empirical case study, it is demonstrated that one cannot uncritically assume that studies funded by the industry and aligned with its commercial interests produce different results than those funded by other sources. Consequently, the article asserts the need to abandon the notion of funding bias and to avoid stigmatizing private research based solely on its origin, as if it were a form of original sin.